2021
DOI: 10.1016/j.seizure.2021.04.022
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocal burden: Adults with drug-resistant epilepsy reflect upon informal caregiver support

Abstract: To explore how a sample of people with uncontrolled seizures describe their experiences of receiving informal supportive care. Methods: Using constructivist grounded theory, in-person, semi-structured interviews were conducted in 35 adults with drug-resistant epilepsy. These 20 (57%) women and 15 (43%) men were aged 18-68 years (mean= 35.6 years), with a range of verbal comprehension scores. The majority, 28 (80%) lived in nuclear family settings. Results: Unpredictable seizures disrupted personal autonomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Our study found that perceived burden was notably high during the pandemic and was related to pandemic-related changes. Burden in the caregiving relationship also appears to be a dyadic experience, with recent findings illustrating mutually burdensome aspects for caregivers and adults with epilepsy, such as reliance on the caregiver, the assumed responsibility of the caregiver on the adult with epilepsy, setting and maintaining boundaries, and protecting one another through caregiver supervision or patient concealment of symptoms [53] . Therefore, maintaining low levels of burden not only holds health and relational implications for both caregiver and recipient, but may also help to enable people living with epilepsy to remain in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that perceived burden was notably high during the pandemic and was related to pandemic-related changes. Burden in the caregiving relationship also appears to be a dyadic experience, with recent findings illustrating mutually burdensome aspects for caregivers and adults with epilepsy, such as reliance on the caregiver, the assumed responsibility of the caregiver on the adult with epilepsy, setting and maintaining boundaries, and protecting one another through caregiver supervision or patient concealment of symptoms [53] . Therefore, maintaining low levels of burden not only holds health and relational implications for both caregiver and recipient, but may also help to enable people living with epilepsy to remain in the community.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients worried about loss of seizure control in a public setting and being a burden to their caregiver [ 6 ]. Indeed, patients may under-report seizures to reduce the stress on caregivers [ 28 ].…”
Section: Seizure Clustersmentioning
confidence: 99%